Optimizing antimicrobial synergy: Green synthesis of silver nanoparticles from Calotropis gigantea leaves enhanced by patchouli oil - Kemala, Pati; Khairan, Khairan; Ramli, Muliadi; Helwani, Zuchra; Rusyana, Asep; Lubis, Vanizra F.; Ahmad, Khairunnas; Idroes, Ghazi M.; Noviandy, Teuku R.; Idroes, Rinaldi (Narra J, 2024)
Silver nanoparticles (AgNPs) synthesized from plant extracts have gained attention for their potential applications in biomedicine. Calotropis gigantea has been utilized to synthesize AgNPs, called AgNPs-LCg, and exhibit antibacterial activities against both Gram-positive and Gram-negative bacteria as well as antifungal. However, further enhancement of their antimicrobial properties is needed. The aim of this study was to synthesize AgNPs-LCg and to enhance their antimicrobial and antifungal activities through a hybrid green synthesis reaction using patchouli oil (PO), as well as to characterize the synthesized AgNPs-LCg. Optimization was conducted using the response surface method (RSM) with a central composite design (CCD). AgNPs-LCg were synthesized under optimal conditions and hybridized with different forms of PO—crude, distillation wastewater (hydrolate), and heavy and light fractions—resulting in PO-AgNPs-LCg, PH-AgNPs-LCg, LP-AgNPs-LCg, and HP-AgNPs-LCg, respectively. The samples were then tested for their antibacterial (both Gram-positive and Gram-negative bacteria) and antifungal activities. Our data indicated that all samples, including those with distillation wastewater, had enhanced antimicrobial activity. HP-AgNPs-LCg, however, had the highest efficacy; therefore, only HP-AgNPs-LCg proceeded to the characterization stage for comparison with AgNPs-LCg. UV-Vis spectrophotometry indicated surface plasmon resonance (SPR) peaks at 400 nm for AgNPs-LCg and 360 nm for HP-AgNPs-LCg. The Fourier-transform infrared spectroscopy (FTIR) analysis confirmed the presence of O-H, N-H, and C-H groups in C. gigantea extract and AgNP samples. The smallest AgNPs-LCg were 56 nm, indicating successful RSM optimization. Scanning electron microscopy (SEM) analysis revealed spherical AgNPs-LCg and primarily cubic HP-AgNPs-LCg, with energy-dispersive X-ray spectroscopy (EDX) confirming silver's predominance. This study demonstrated that PO in any form significantly enhances the antimicrobial properties of AgNPs-LCg. The findings pave the way for the exploration of enhanced and environmentally sustainable antimicrobial agents, capitalizing on the natural resources found in Aceh Province, Indonesia.